PENGARUH KOMPETENSI, REWARD DAN PENGEMBANGAN KARIR TERHADAP KINERJA DOSEN STIE TRISNA NEGARA - Helisia Margahana (ITB AAS INDONESIA Surakarta, 2020)
The purpose of this study was to determine and prove the effect of the independent variables, namely competence, reward and career development, on the dependent variable, namely the performance of Lecturer STIE Trisna Negara simultaneously and partially. The methodology of this research uses quantitative descriptive. The research was conducted at STIE Trisna Negara, Belitang with a population of 55 and a total sample of 45 respondents. The sampling method uses saturated samples. Measurement in the questionnaire uses a Likert scale. The data analysis method used in this research is instrument test, classical assumption test and hypothesis testing (multiple linear regression analysis, F test, t test, and coefficient of determination) with the help of SPSS version 24 program. The results of this study indicate that the competency variable, Rewards and career development have a positive effect simultaneously on the lecturer performance of STIE Trisna Negara, Belitang. Competence partially has a positive and significant effect. Meanwhile, rewards and career development partially do not affect the performance of STIE Trisna Negara lecturers. Keywords: Performance, Competence, Career Development, Reward